Freeze-Dried Banana Slices Carrying Probiotic Bacteria - Niro, Carolina M.; Mendonça, Giovana M. N. [UNESP]; Paulino, Lucca R.; Soares, Viviane F.; Azeredo, Henriette M. C. (MDPI, 2023)
Findings on diet–health relationships have induced many people to adopt healthier diets, including the substitution of energy-dense snacks with healthier items, e.g., those containing probiotic microorganisms. The aim of this research was to compare two methods to produce probiotic freeze-dried banana slices—one of them consisting of impregnating slices with a suspension of probiotic Bacillus coagulans, the other based on coating the slices with a starch dispersion containing the bacteria. Both processes resulted in viable cell counts above 7 log ufc.g−1, although the presence of the starch coating prevented a significant loss in viability during freeze-drying. The coated slices were less crispy than the impregnated ones, according to the shear force test results. However, the sensory panel (with more than 100 panelists) did not perceive significant texture differences. Both methods presented good results in terms of probiotic cell viability and sensory acceptability (the coated slices being significantly more accepted than the non-probiotic control slices).
Keywords: edible coatings; polysaccharides; tropical fruits